What is the answer of c) and d)
Attachments:
![](https://hi-static.z-dn.net/files/dbd/c81bb3aece391d0999fc35dd703d93f4.jpg)
Answers
Answered by
0
Answer:
answer for c
answer for d
Step-by-step explanation:
sjsk
oso
eieoiddof
ifdo.fodod
official zkw
Answered by
0
Answer:
Step-by-step explanation:
c) L.H.S = 2/3 j = 2/3×5/6 = 5/9 = 40/72
R.H.S = 1/4 + 2/3 - j/3 = 11/12 + 5/18 = 86/72
Hence ;
L.H.S ≠ R.H.S
so , the given solution does not satisfy
d) L.H.S = 6x- 4x = 6×(-2) - 4(-2) = -12 + 8 = (-4)
R.H.S = 2x = 2(-2) = (-4)
Hence,
L.H.S = R.H.S
so the solution satisfies the above equation
Similar questions